THE IMPACT OF ENTREPRENEURSHIP ORIENTATION AND DIGITAL TRANSFORMATION ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES - Yadewani, Dorris; Toni Parlindungan S, Gokma; Wijaya, Reni (Universitas Riau Kepulauan, 2025)
This research examines the influence of entrepreneurial orientation and digital transformation on small and medium enterprises (SMEs) performance in Padang City. The research method used is quantitative, with a descriptive approach and statistical analysis. The research sample consisted of 40 owners and/or employees of SMEs in Padang City, selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using SPSS 22. The research results show that entrepreneurial orientation has a positive and significant impact on the performance of SMEs. On the other hand, digital transformation hurts the performance of SMEs. Multiple linear regression analysis shows that these two independent variables simultaneously have a significant impact on SME performance. This research provides empirical contributions to the existing literature and emphasizes the importance of entrepreneurial orientation and proper digital transformation management in improving SME performance. Furthermore, this research provides empirical evidence on the impact of entrepreneurial orientation and digital transformation on the performance of small and medium enterprises, which can contribute to the understanding of the importance of entrepreneurial orientation and the use of technology to enhance the performance of small and medium enterprises.